PENERAPAN TEKNIK KONSERVASI TANAH DAN AIR DAN FAKTOR SOSIAL EKONOMI YANG MEMPENGARUHINYA DI DAERAH TANGKAPAN AIR SUNGAI NANGGALA DAS SADDANG - Adelheith Mangatta; Wahyuni wahyuni; Andang Suryana Soma; Usman Arsyad; Baharuddin Mappangaja (Program Studi Kehutanan Universitas Muslim Maros, 2020)
Soil and Water Conservation is an effort to protect, restore, improve, and maintain the function of the land by the capabilities and allotment of land to support sustainable development and sustainable living. This study aims to identify and assess the proper use of soil and water conservation techniques applied by farmers based on the assessment guidelines for soil and water conservation techniques and their relationship with socioeconomic factors that influence the actions of Soil and Water Conservation. Methods of direct observation in the field both in the form of surveys and in the way of interviews with farmers who apply soil and water conservation techniques. Data collected from socioeconomic factors such as age, level of education, income, number of family dependents, and area of ​​arable land. The data is processed by contingency techniques then classified and tested in chi-square.The results of this study indicate that the application of soil and water conservation techniques in The Catchment area of Nanggala river in the form of vegetative methods is applied in the way of cover crops, yards, and mixed gardens, while mechanical methods in the form of bench terraces. The application of soil and water conservation techniques by farmers is 67.75% correct, 9.67% somewhat proper, and 22.58% incorrect. Soil and water conservation techniques do not have a real relationship with socioeconomic factors.